DESIGN AND DEVELOPMENT OF MEDICANE PROCUREMENT APPLICATION IN RSI JEMURSARI SURABAYA - Muhamad Fikri; Dewiyani Sunarto; Pantjawati Sudarmaningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The pharmacy installation at Jemursari Hospital in Surabaya tasked with serving the patient’s medical needs. There are several problems in pharmaceutical installations today, one of which is management of medicane procurement. For now the management of medicane procurement at the RSI Surabaya is based on estimated, this cause uncertainy how many medicinal products must be ordered, and when the time for ordering medicane. In addition, the uncertain number of medicane request every week result in confusing in the pharmaceutical departement in procuring medicane. The solution of the problem is making a medicane procurement application that will help the pharmaceutical departement to procure medicane in the future. The information provided to the pharmaceutical departement will be in the form of forecasting the procurement of medicane using the double exponential smoothing method. Provides information when the medicane must be ordered again using the Reorder Point (ROP) method. Provide minimum stock information that must be available in the warehouse using the safety stock method. For application design using the SDLC method. Based on the result of application testing that uses the black-box testing method with sellenium tools using 22 data test case, 100% results are obtained so that the application for determining medicane procurement is in accordance with the needs of the hospital.